2010
DOI: 10.1021/ja103786c
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic C−H Bond Functionalization via Tandem 1,5-Hydride Transfer/Ring Closure: Asymmetric Synthesis of Tetrahydroquinolines

Abstract: The first organocatalytic enantioselective intramolecular 1,5-hydride transfer/ring closure reaction is described. This redox neutral reaction cascade allows for the efficient formation of ring-fused tetrahydroquinolines in high enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(73 citation statements)
references
References 57 publications
0
72
0
1
Order By: Relevance
“…[89] Indeed, the intramolecular reaction of a series of cinnamaldehyde derivatives 179a-e provided the corresponding ringfused tetrahydroquinolines 180a-e in moderate to excellent enantioselectivities of up to 99% ee combined with generally moderate yields and diastereoselectivities. A remarkable result was obtained for tetrahydroisoquinoline 179f.…”
Section: Domino Michael-intramolecular Alkylation Reactionsmentioning
confidence: 99%
“…[89] Indeed, the intramolecular reaction of a series of cinnamaldehyde derivatives 179a-e provided the corresponding ringfused tetrahydroquinolines 180a-e in moderate to excellent enantioselectivities of up to 99% ee combined with generally moderate yields and diastereoselectivities. A remarkable result was obtained for tetrahydroisoquinoline 179f.…”
Section: Domino Michael-intramolecular Alkylation Reactionsmentioning
confidence: 99%
“…However, the use of Lewis acids considerably accelerated [26,[58][59][60][61] cyclization by the tert-amino effect mechanism and made it possible to extend the applicability of the reaction [26,61]. It was also shown that using such acids as trifluoroacetic, HCl, HBr or (-)-camphorsulfonic acid allowed to cyclize the vinyl derivatives 72 containing only one withdrawing group at the double bond [57,62]. It was noted in the review [3] that for cyclization without a catalyst there should be at least two electron-withdrawing substituents in the vinyl group.…”
Section: -100%mentioning
confidence: 99%
“…[4] Among the reported transformations, intramolecular redox processes for the direct functionalization of C sp 3 ÀH bonds that are a to heteroatoms are important for the synthesis of structurally diverse amine and ether derivatives. [5] Furthermore, since the pioneering work of Kim and co-workers, [6] there have many good results reported in the area of intramolecular redox processes for the direct enantioselective C sp 3 À H functionalization at positions a to nitrogen atoms. [7] However, examples of the corresponding enantioselective reaction of ethers are scarce.…”
mentioning
confidence: 99%
“…[10] The presence of a counterion that is more weakly coordinating than ClO 4 À would lead to an iminium ion with enhanced electrophilicity (Scheme 1), thus accelerating the hydride shift. The weakly coordinating anions, BF 4 À and SbF 6 À , have been effective for many catalytic reactions. [11] Therefore, substrate 1 a was treated with 7 (the hydrochloride salt of 6) together with either AgBF 4 or AgSbF 6 (Table 1, entries 7 and 8).…”
mentioning
confidence: 99%